Undocumented Migration as a Theologizing Experience : Religious Stories Korean American Dreamers Tell in the Face of Uncertainty - Cho, Eunil David (Religious Studies, Theology and Philosophy E-Books Online, Collection 2025., 2025)
In Undocumented Migration as a Theologizing Experience , Eunil David Cho examines how Korean American undocumented young adults tell religious stories to cope with the violence of uncertainty and construct new meanings for themselves. Based on in-depth interviews guided by narrative inquiry, the book follows the stories of ten Korean American DACA (Deferred Action for Childhood Arrivals) recipients who have found their lives in limbo. While many experience narrative foreclosure, believing "My story is over," Cho highlights how telling religious stories enables them to imagine and create new stories for themselves not as shunned outsiders, but as beloved children of God.